INFOGENE: a database of known gene structures and predicted genes and proteins in sequences of genome sequencing projects. - Solovyev, V V (1999)
INFOGENE is a database of known and predicted gene structures with descriptions of basic functional signals and gene components. It provides a possibility to create compilations of sequences with a given gene feature as well as to accumulate and analyze predicted genes in finished and unfinished sequences from genome sequencing projects. Protein sequence similarity searches in the database of predicted proteins is offered through the BLASTP program. INFOGENE is realized under the Sequence Retrieval System that provides useful links with the other informational databases. The database is available through the WWW server of the Computational Genomics Group at http://genomic.sanger.ac.uk/db.html